Transition of Treatment for Ground Glass Opacity–Dominant Non-Small Cell Lung Cancer - Handa, Yoshinori; Tsutani, Yasuhiro; Okada, Morihito (Frontiers in Oncology, 2021)
Lobectomy has been the standard surgical treatment for non-small cell lung cancer (NSCLC). Over the decades, with the dramatic development of radiographic tools, such as high-resolution computed tomography (HRCT), and the widespread practice of low-dose helical CT for screening, the number of cases diagnosed with small-cell lung cancers with ground glass opacity (GGO) at early stages has been increasing. Accordingly, mainly after 2000, many retrospective studies and prospective trials have shown that patients with lung adenocarcinoma with GGO have a good prognosis and may be candidates for sublobar resection. Previous studies indicated that HRCT findings including the maximum diameter of the tumor, GGO ratio, and a consolidation/tumor ratio (CTR) are simple and useful tools to predict tumor invasiveness and prognosis in patients with NSCLC with GGO. Thus, sublobar resection may be considered a “standard therapy” for peripheral GGO-dominant small-cell lung adenocarcinomas. Ultimately, some of such tumors might not require surgical resection. A multicenter, prospective study has just begun in Japan to evaluate the validity of follow-up for small-sized GGO-dominant small-cell lung cancer. Lung cancers that do not require surgery should be identified. This study reviewed retrospective and prospective studies on GGO tumors and discussed the treatment strategies for such tumors.